2003
DOI: 10.1172/jci200317490
|View full text |Cite
|
Sign up to set email alerts
|

The role of falling leptin levels in the neuroendocrine and metabolic adaptation to short-term starvation in healthy men

Abstract: To elucidate the role of leptin in regulating neuroendocrine and metabolic function during an acute fast, six to eight healthy, lean men were studied under four separate conditions: a baseline fed state and three 72-hour fasting studies with administration of either placebo, low-dose recombinant-methionyl human leptin (r-metHuLeptin), or replacement-dose r-metHuLeptin designed to maintain serum leptin at levels similar to those in the fed state. Replacement-dose r-metHuLeptin administered during fasting preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
276
2
20

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(311 citation statements)
references
References 57 publications
13
276
2
20
Order By: Relevance
“…In lean healthy subjects, the circadian rhythms of TSH and leptin are superimposable (45), and the subcutaneous administration of leptin significantly blunts the fall of TSH secretion induced by prolonged fasting (46). These findings indicate that leptin has a regulatory effect on TSH secretion.…”
Section: The Leptin-thyroid Relationshipmentioning
confidence: 71%
“…In lean healthy subjects, the circadian rhythms of TSH and leptin are superimposable (45), and the subcutaneous administration of leptin significantly blunts the fall of TSH secretion induced by prolonged fasting (46). These findings indicate that leptin has a regulatory effect on TSH secretion.…”
Section: The Leptin-thyroid Relationshipmentioning
confidence: 71%
“…Chan et al showed that a period of 72-h fasting in healthy men induces a decrease in serum T 3 by 30%, and a marked suppression of TSH secretion with a decrease in integrated area by over 70% as well as loss of the typical pulsatility characteristics observed in the fed state. Interestingly, administration of a replacement dose of leptin designed to maintain serum leptin at levels similar to those in the fed state largely prevented the starvationinduced changes in the HPT axis (7). In addition to these changes at the central level of the HPT axis during food deprivation, peripheral TH metabolism is also affected by fasting.…”
Section: Feeding Statusmentioning
confidence: 99%
“…However, already in the 1980s, it became clear that a variety of illnesses, including myocardial infarction, sepsis and surgical procedures, cause a decrease in serum triiodothyronine (T 3 ) levels and -in severe cases -T 4 , without an elevation in TSH. Since then, additional examples of exogenous factors (schematically represented in Within the circle, the HPT axis setpoint is driven mainly by TRH physiological factors include the diurnal TSH rhythm with a clear nocturnal TSH surge (6), which is driven by the hypothalamic suprachiasmatic nucleus (SCN), and prolonged fasting, which induces a decrease both in serum T 3 (by 30%) and serum TSH (by 70%) in healthy men (7). By inference, feeding status and time-of-day effects should be considered in careful interpretation of serum TSH in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is secreted from adipocytes into the bloodstream in proportion to body fatness, and signals energy sufficiency and acts on the hypothalamus to suppress feeding and increase energy expenditure. Serum leptin concentrations change gradually over time in response to changes in fat mass, but fall rapidly in response to complete fasting (Boden et al 1996, Chan et al 2003, and this fall in leptin concentration is thought to mediate reproductive suppression due to nutritional stress. For example, preventing the starvation-induced fall in leptin with exogenous leptin was shown to prevent the starvation-induced delay in ovulation in female mice (Ahima et al 1996).…”
Section: Leptinmentioning
confidence: 99%